2020
DOI: 10.1371/journal.pone.0229611
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between histogram-based DCE-MRI parameters and 18F-FDG PET values in oropharyngeal squamous cell carcinoma: Evaluation in primary tumors and metastatic nodes

Abstract: Objectives To investigate the correlation between histogram-based Dynamic Contrast-Enhanced magnetic resonance imaging (DCE-MRI) parameters and positron emission tomography with 18 F-fluorodeoxyglucose (18 F-FDG-PET) values in oropharyngeal squamous cell carcinoma (OPSCC), both in primary tumors (PTs) and in metastatic lymph nodes (LNs). Methods 52 patients with a new pathologically-confirmed OPSCC were included in the present retrospective cohort study. Imaging including DCE-MRI and 18 F-FDG PET/CT scans were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…The possible impact of HPV status on DCE-MRI parameters was also investigated. Consistent with earlier literature, any difference in vascularity was reported based on HPV status for primary tumors and lymph nodes [36,42,43].…”
Section: Discussionsupporting
confidence: 87%
“…The possible impact of HPV status on DCE-MRI parameters was also investigated. Consistent with earlier literature, any difference in vascularity was reported based on HPV status for primary tumors and lymph nodes [36,42,43].…”
Section: Discussionsupporting
confidence: 87%
“…For the reference standard, the main concern was the use of different HPV determination methods for different patients or the exclusive use of p16 immunohistochemistry for HPV determination [ 20 , 21 , 22 , 23 , 26 , 31 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. The main concern for patient selection was the lack of information on consecutive or random patient selection and the exclusion of patients with lower-stage OPSCC [ 20 , 25 , 27 , 35 , 36 , 37 , 38 , 39 , 45 , 46 , 47 ]. Regarding the index test, the main concern was the lack of pre-specification of thresholds or independent validation [ 21 , 25 , 26 , 27 , 31 , 39 , 40 , 41 , 46 , 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-one studies had a retrospective cohort study design [2,[19][20][21][22]25,26,28,29,31,32,35,[37][38][39]42,44,45,[47][48][49], and seven studies had a prospective cohort study design [23,27,40,41,43,46,50]. Of the twentyeight included papers, five papers focused on structural MRI sequences that were used in routine clinical examinations [19][20][21][22][23], nineteen focused on DWI sequences [2,25,[27][28][29]31,32,35,36,38,39,41,42,[44][45][46][47]...…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…[54][55][56] Several studies evaluated the relationships between DCE-MRI and 18F-FDG-PET/CT parameters in primary HN tumors and metastatic LNs. [57][58][59][60] Vidiri et al 61 studied 52 patients with a new pathologically confirmed OP-SCC using DCE-MRI and 18F-FDG-PET/CT imaging methods. The group researched the PTs and the largest LN using quantitative DCE-MRI parameters including the transfer constants, K trans and k ep , and the volume of EES, V e (Fig.…”
Section: Correlation Between Dce-mri Parameters and 18f-fdg In Oropha...mentioning
confidence: 99%